Effectiveness of 20 weeks of non-invasive electrical vestibular nerve stimulation in the management of obesity in adolescents - Nithiya K,; Vinothini M,; Deepan Suresh V,; Sai Sailesh Kumar Goothy, (Asian Journal of Medical Sciences, 2025)
Background: The number of cases of obesity has been rising worldwide due to the current lifestyle and unhealthy food habits. The vestibular system has connections with various brain areas involved in the regulation of food intake. Stimulating the vestibular system by non-invasive means has multiple benefits. However, the studies in this area are relatively less. Hence, the present study was undertaken. Aims and Objectives: The present study was undertaken to observe the effectiveness of non-invasive electrical vestibular nerve stimulation in the management of obesity. Materials and Methods: The present study was an experimental study where a total of 30 male and female participants were part of the study. After recording the baseline values, participants underwent non-invasive electrical vestibular nerve stimulation for 20 weeks. Post-intervention values were recorded after completion of 20 weeks. Body weight was recorded using a digital weighing machine cult smart scale. Body mass index (BMI) was calculated using a BMI calculator available online. Eating behavior was assessed using a standard questionnaire Eating Attitude Test 26 (EAT-26). Results: There was a significant decrease in the body weight, BMI and EAT-26 score followed by the 20 weeks of intervention in both males and females. No serious adverse effects were noted. Conclusion: The current study results support the implementation of non-invasive electrical vestibular nerve stimulation in combination with a lacto-vegetarian diet in the management of obesity. Further, the study presents that non-invasive electrical vestibular nerve stimulation is safe to use in a long-term basis.